PEMODELAN MATEMATIKA LAJU ALIRAN PANAS PADA WAJAN PEMBUATAN ARANG AKTIF-13 DENGAN MENGGUNAKAN METODE BEDA HINGGA (FINITE DIFFERENCE METHOD) - Tiryono R,; Nurhayati, Nurhayati; Dorrah A,; Aang N, (Journal of Innovation Research and Knowledge, 2023)
In this paper we propose the theory of finite difference methode for calculating heat transfer on rectangular tin pan alloy which the center temperature is 7000c and the ambien temperature is 300 c. The aim in this paper we used this method for calculating of heat transfer on the pan in order to process of making activated charcoal especially called “arang aktif-13”. We design a furnace which is the heat resources in the center only then choosing 9 points rectangularly on the plate pan that it will be calculated the value of temperature and the velocity of temperature on these points. By assumption the temperature at the center of the pan on the furnice is consistence or stable, then we do the process of defried of row material coconut shell until cooked as activated charcoal. We consider choosing 9 points in order tobe caculated as manually easiely and therefore can be comparing with using software lindo, and also for more points grather than 9 we suggested using masine more efficient. The spreading of the heat on the plate pan when the moment achieve the condition of the temperature araund the pan stable, then it can be animated by using software matlab. By doing depried of row material, that process will need 13 minutes to become activated charcoal.